RELIGION AND NATIONAL INTEGRATION - Francis, K C (Journal of Dharma, 2000)
All religion, theoretically and doctrinally teach universal love, peace, harmony, human solidarity and unity. But paradoxically some of the fiercest battles in the history of the world were waged in the name of religion. The religions have divided humankind into different camps, erecting walls of separation between them and fostering mutual suspicion, distrust rivalry, fanaticism, suppression and persecution. In Asia, the case of Sri Lanka is striking for its cruelty because two identities are in confrontation, one Sinhalese and Buddhists and the other, Tamil and nationalist. India is in the grips of twofold conflict between the fundamentalist Hindus and the minority communities (Muslim and Christians) on the one hand, and between the superior castes and the Dalits on the other. In Africa, Algeria offers the everyday spectacle of killing in the name of religious orthodoxy. In Rwanda where in just three months a million were left dead and more than twice as many were driven out of their homes, and some of the Catholic clergy have been seriously implicated in it. Commenting on the atrocities committed in the name or religion in Rwanda, it was said: "There are no devil left in hell, they are all in Rwanda."